Phytochemical analysis and protective effects of Vaccinium macrocarpon (cranberry) in rats (Rattus norvegicus) following ethylene oxide-induced oxidative insult. Issue 1 (1st January 2021) - Rasool, Mahmood; Malik, Arif; Abdul Basit Ashraf, Muhammad; Mubbin, Rabia; Ayyaz, Ujala; Waquar, Sulayman; Asif, Muhammad; Umar, Muhammad; Siew Hua, Gan; Iqbal, Zafar; Alam, Hina; Achakzai, Niaz M.
ABSTRACT: The Vaccinium genus comprises more than 126 genera of perennial flowering plants that are commonly adapted to poor and acidic soils or epiphytic environments. Their molecular and genomic characterization is a result of the recent advent in next-generation sequencing technology. In the current research, extracts were prepared in different media, such as petroleum ether, methanol and ethanol. An extract of Vaccinium macrocarpon (cranberry) was used at a dose of 200–400 mg/kg by weight (B.wt). Levels of oxidative stress markers, i.e., superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), advanced oxidation protein products (AOPPs) and malondialdehyde (MDA), were measured. A histopathological study of six vital organs in rats was also conducted. The results indicated that the antioxidant levels were lower in the group given only ethylene oxide (EtO) but higher in the groups receiving cranberry extract as a treatment. Major improvements were also observed in stress markers such as advanced oxidation protein products (AOPPs) and MDA following cranberry treatment. Histopathological changes induced by EtO were observed in the heart, kidney, liver, lung, stomach and testis and were reversed following cranberry treatment. The major toxic effects of EtO were oxidative stress and organ degeneration, as observed from various stress markers and histopathological changes. Our study showed that this extract contains strong antioxidant properties, which may contribute to the amelioration of the observed toxic effects. GRAPHICAL ABSTRACT: uf0001